FNIH-defined Sarcopenia Predicts Adverse Outcomes Among Community-Dwelling Older People in Taiwan: Results From I-Lan Longitudinal Aging Study. (25th July 2017) - Tang, Ting-Ching; Hwang, An-Chun; Liu, Li-Kuo; Lee, Wei-Ju; Chen, Liang-Yu; Wu, Yi-Hui; Huang, Chung-Yu; Hung, Cheng-Hao; Wang, Chih-Jen; Lin, Ming-Hsien; Peng, Li-Ning; Chen, Liang-Kung
Abstract: Background: To evaluate the predictive validity of sarcopenia defined by the Foundation for the National Institutes of Health (FNIH) Sarcopenia Project among Asian older adults. Methods: Data of the I-Lan Longitudinal Aging Study were obtained for analysis. Overall, 1, 839 community-dwelling people aged 50 years and older, capable of completing a 6-m walk, with life expectancy of more than 6 months, and not institutionalized at time of data collection were enrolled for study. Data for subjects aged 65 years and older were obtained for study. The outcome measures were all-cause mortality and a composite adverse outcome which includes hospitalizations, emergency department visits, institutionalization, and falls. Results: Data of 728 eligible elderly participants (73.4 ± 5.4 years; 52.9% males) were analyzed. The prevalence of FNIH-diagnosed sarcopenia was 9.5%: 11.9% males; 6.7% females. Participants having FNIH-defined sarcopenia were considerably older, frailer, more obese, with poorer physical performance than nonsarcopenic subjects (All p < .001); during mean follow-up of 32.9 ± 8.8 months, they also had 3.8 times higher risk of dying, independent of age, sex, multimorbidity, cognitive function, and nutritional status (hazard ratio = 3.8; 95% confidence interval = 1.26–11.45; p = .018). Moreover, sarcopenia defined by grip strength-BMI ratio (WeakBMI ) showed stronger association with composite adverse outcomes than traditional handgrip strength (hazard ratio = 1.99; 95% confidence interval = 1.01–3.93; p = .047 vs hazard ratio = 1.80; 95% confidence interval = 0.89–3.62; p = .102 in fully-adjusted model). Conclusion: Among community-dwelling older people in Taiwan, participants with FNIH-defined sarcopenia had a significantly greater risk of all-cause mortality and composite falls, emergency department visits, institutionalization, and hospitalization.